Histological changes in pituitary-testes axis in rats exposed to cadmium chloride: Protective role of Eruca sativa seeds: Baraa Najim Al-Okaily1 and Zenah Mohammed Al-Shammari2 - Al-Okaily, Baraa Najim (The Iraqi Journal of Veterinary Medicine, 2017)
The present study was carried out to investigate the protective effect of Eruca sativa seeds against changes of pituitary and testes in cadmium treated rats. Forty adult male albino rats were used and divided into 4 equal groups and treated for 8 weeks as follow: The first group was given distilled water and used as a control group. The second group (G1) was administered tap water containing 30 ppm/ L of cadmium chloride. Animals in third group (G2) received tap water containing Cadmium chloride as in G1 plus 250 mg/Kg B.W ethanolic extract of Eruca sativa seeds, while rats in fourth group (G3) administered 250 mg/Kg B.W of ethanolic extract of Eruca sativa seeds only. After 8 weeks of experiment the animals were anesthetized, the pituitary and testes were excised for histological studies. Results showed that cadmium chloride intake caused severe alterations in the pituitary gland manifested by a marked apoptotic cells of pars distalis, accompanied with marked necrosis leading to left large multiple spaces in their parenchyma. Whereas testes revealed shrinkage, irregular arrangement of seminiferous tubules and increase intertubular spaces. A considerable changes was also found in the seminiferous tubules with loss most of their epithelial layer and filled with cellular debris, incomplete spermatogenesis, congested blood vessels and few Leydig's cells. Administration of Eruca sativa extract reduce the deleterious effects of cadmium chloride on pituitary gland as well as more or less complete spermatogenesis process with thickness of interstitial tissue in most of seminiferous tubules. It could be suggested that the antioxidant properties of Eruca sativa extract protects the deleterious histological damage induced by cadmium chloride in adult rats.